(untitled) (Journal of Humanitarian and Applied Sciences, 2024)
Praise be to Allah who honored the Arabic language and made it the language of the Qur’an, and the language of the people of Paradise on the day of meeting in Paradise, and that he chose us from among His worshippers who were preoccupied with its beautiful arts and methods, looking forward to tasting its words that combine clarification, and hoping to fear God and straighten the tongue. May blessings and peace be upon our teacher and Prophet Mohammad, peace and blessings of Allah be upon him, the imam, the bearer of the banner of praise in the shadow of the Throne of the Most Gracious, the owner of the Chosen Position and the blessed basin, the master of the ancients and the lasts in existence. His Lord commanded him to challenge the rhetoricians and legends throughout the ages, and He said to him: “Say, "Bring you then ten forged Surah (chapters) like unto it, and call whomsoever you can, other than Allah (to your help), if you speak the truth” [Hud: 13]. Having said that... I present to the reader a study entitled: “Increasing some imperfect verbs and some perfect verbs in structure”; To discuss the addition of "was", along with its sisters: "became ", and some verbs: the past and the perfect imperative according to those who say its addition, trying to investigate its evidence from prose texts and poetic evidence. The motivation for researching it is that the addition is considered a style of language, one of its many types, and one of its distinct features, with which the Holy Qur’an was revealed to raise its slogan: one world and another, a challenge and a miracle. The addition is one of the established principles of the Arabic language, and the evidence for it in some of its types is many and extensive, and it is not one and the same, and the statement about its addition was scattered statements in the books of grammar, language, interpretation, principles, and others. The increase in the letters of meanings is many and steady, in the verbs it is few, and in the nouns relatively les . Through collecting the material, examining the texts, and processing the evidence related to the research, the methodology required that the plan proceed according to an introduction, a preface, two sections, each of which has demands, a conclusion with the most important results and recommendations, then an index of sources and references.